Bronchodilators for treatment of mild bronchiolitis: a factorial randomised trial. Issue 3 (March 1992) - Wang, E E; Milner, R; Allen, U; Maj, H
Abstract : A randomised double blind trial was conducted to determine the efficacy of inhaled bronchodilators, salbutamol and ipratropium bromide, compared with placebo in the treatment of bronchiolitis. Patients, who were 2 months to 2 years of age and without underlying cardiac or pulmonary disease, received drug 1 (salbutamol or saline placebo) followed one hour later by drug 2 (ipratropium bromide or placebo). Both agents were administered every four hours. The patients were allocated to one of four groups according to a factorial design. The four groups were similar in demographic characteristics, initial oxygenation, and clinical score. The change in oxygen saturation of recipients of both agents was significantly better than that of recipients of salbutamol alone or ipratropium bromide alone. This change, however, was not statistically different from that of the control group. No difference was observed in the clinical score or hospital duration. Inhaled bronchodilators did not improve the condition of hospitalised mild bronchiolitis.